Syriac Jacobite and Coptic Churches as representatives of Eastern christianity - Shepetyak, Oksana Tarasivna (Ukrai͏̈ns'ke relihijeznavstvo, 2017)
The article deals with analysis of the formation and historical significance of two traditions in Eastern Christianity, which emerged as a result of the rejection of theological decisions of the Chalcedon Ecumenical Council, that means, they adopted into their own theological tradition significant influences of monophysitism. This concerns Syriac Jacobite and Coptic Churches, as well as the churches that are associated with them in historical and theological cognation.